Organizational communication and corporate social responsibility. Case study: Romanian vs. International CSR - Luchenciuc Elena-Georgiana,; Mihaela Rus,; Tasente, Tanase (Technium Social Sciences Journal, 2020)
When we say "Organizational communication", we think, unconsciously, about organizations and how they are influenced by the effectiveness of communication both between team members and the external environment. Because the world revolves around ideas, concepts and communication strategies well developed for the purpose of informing, helping or even manipulating local and global communities, the paper will emphasize the importance of Corporate Social Responsibility (CSR) campaigns and how they influence the environment in the context of sustainable development, various categories of public or the image gained from such an initiative as they may represent a smart strategy to repair a stained name. To emphasize the importance of CSR, we will present some campaigns initiated by an the organization of the food and drink industry, both in Romania and internationally, between 2016-2018. Through this research, we set out to identify the main social responsibility campaigns of the organization, the main areas of action of the social responsibility campaigns and to establish comparative analysis between the particularities of the CSR campaigns in Romania and internationally.